Role of RDW in Prediction of Burn after Caustic Substance Ingestion - Emrah Aydin; Omer Faruk Beser; Soner Sazak; Ensar Duras (MDPI AG, 2017)
A quantifiable, quick, inexpensive and reproducible predictor is needed to decide if caustic substance ingestion results in burn regardless of the symptoms. A multicenter cohort study was conducted to investigate the predictive value of red cell distribution width (RDW) in detecting the esophageal burns. The data of 174 patients were retrospectively analyzed. Eleven patients were excluded due to inability to define the substance ingested. Complete blood count (CBC) was taken at admission, and an esophagogastroduodenoscopy was performed within the first 12-24 h in all patients, regardless of their symptoms. The age and gender of the patients, the types of substances ingested, the parameters in the CBC and the severity of the esophageal injury were correlated. Esophageal burns were diagnosed in 38 of 163 patients (23.3%). The risk of esophageal burn with RDW values below 12.20 was significantly lower. Multivariate analysis showed that RDW was the most significant predictor of esophageal burn (p = 0.000, odds ratio (OR) 7.74 (95% confidence interval (CI), 3.02-19.9)). Receiver operating characteristic (ROC) curve analysis demonstrated 84.2% sensitivity at a cut-off value of 12.20 for RDW. The results showed that CBC parameters could avoid unnecessary esophagogastroduodenoscopy. The RDW values regardless of the symptomatology is a good predictor of esophageal burns, and an RDW value over 12.20 shows the increased risk of esophageal burn.